Electrophysiological brain functional network alterations associated with hippocampal volume in healthy and pathological aging. (1st February 2022) - Torres, Lucia; Cuesta, Pablo; Fernández, Ricardo Bruña; Vilca, Brenda Chino; Dolado, Alberto Marcos; Fuertes, Miguel Yus; Arrazola, Juan; Fernandez, Alberto; Verdejo, Juan; Maestú, Fernando; Higes, Ramón López
Abstract: Background: The early detection of Alzheimer disease is currently one of the main worldwide scientific goals. Estructural biomarkers, such as cortical deterioration and medial temporal lobe atrophy (MTLa), are well known and deeply studied. The relation of these structural changes with brain connectivity could help to understand the consequences of neurodegeneration in brain functioning, with the ultimate goal of explaining cognitive impairment. Magnetoencephalogram (MEG) quantitative analysis is a precise, non‐invasive tool to evaluate changes in bioelectrical activity of the brain. Therefore, it brings us the opportunity to study disruption of functional brain networks associated with changes in MTLa volume, as assessed with structural MRI. Method: We recruited 376 healthy elders and 130 mild cognitive impairment patients (MCI) (aged from 61 to 85) from the "Hospital Universitario San Carlos" and the Center for elders at the Chamartín District, all located in Madrid, Spain. All of them underwent a neuropsychological evaluation, MRI assessment, and MEG recordings. The MCI diagnosis was established according to the NIA‐AA criteria. None of the participants exhibited a history of psychiatric or neurological disorders (other than MCI). We used a completely data‐driven approach to evaluate the relationship between functional connectivity (FC) and the hippocampal volume. Result: Our main finding was an augmented theta band functional connectivity (FC) in right temporal (RTemp) areas associated with lower hippocampal volume, and we found this FC signature to correlate negatively with memory performance. Furthermore, the average theta FC of this area differed significantly between groups, although the original relationship remained significant for each group independently. Finally, we performed a seed‐based analysis targeting the original right temporal region and found that the modulation of the theta FC was driven by connections to 1) superior frontal and 2) contralateral temporal areas. Conclusion: The results depict a clear FC pattern that seems to be associated with both healthy and pathological aging. This MEG signature may be useful as a non‐invasive biomarker for the progressive subcortical degeneration that occurs along aging, both healthy and pathological. Furthermore, it is also related with cognitive performance, especially with memory functioning.